In Vitro Activity of Finafloxacin against Panels of Respiratory Pathogens - Sarah V. Harding; Kay B. Barnes; Stephen Hawser; Christine E. Bentley; Andreas Vente (MDPI AG, 2023)
This study determined the in vitro activity of finafloxacin against panels of bacterial strains, representative of those associated with infection in cystic fibrosis patients and predominately isolated from clinical cases of respiratory disease. Many of these isolates were resistant to various antimicrobials evaluated including the aminoglycosides, cephalosporins, carbapenems and fluoroquinolones. Broth microdilution assays were performed at neutral and acidic pH, to determine antimicrobial activity. Finafloxacin demonstrated superior activity at reduced pH for all of the bacterial species investigated, highlighting the requirement to determine the activity of antimicrobials in host-relevant conditions.